Complementary EIS/FTIR study of the degradation of adhesives in electronic packaging. Issue 11 (8th June 2020) - Schneider, Michael; Gierth, Uta; Simunkova, Lenka; Gierth, Paul; Rebenklau, Lars
Abstract: Adhesives are widely used in electronic packaging and are of vital importance in the reliability of electronic systems. A deep understanding of the degradation mechanism of adhesives under corrosion load plays a key role in lifetime prediction. Unfortunately, most of the common reliability tests are destructive. The present approach combines the nondestructive methods, electrochemical impedance spectroscopy and the Fourier‐transform infrared spectroscopy, as powerful tools in a complementary manner to describe the degradation mechanism and kinetics of two epoxy‐based adhesives, which are commonly used in electronic packaging. It is demonstrated that the application quality is the dominating impact on the optimization of the lifetime. Abstract : The present approach combines the nondestructive methods, electrochemical impedance spectroscopy and Fourier‐transform infrared spectroscopy, as powerful tools in a complementary manner to describe the degradation mechanism and kinetics of two epoxy‐based adhesives, which are commonly used in electronic packaging. It is demonstrated that the application quality has a dominant impact on the optimization of the lifetime.